Dampak Media Sosial Tiktok Terhadap Perkembangan Psikologis Remaja: Menurut Prespektif Teori Kroh - Suparmi , Suparmi; Virliana, Asya Izzati; Yogi, Rihadatul Aisha Widya (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2024)
This study analyzes the impact of TikTok social media on adolescent psychological development using Kroh's theory as a reference framework. The development of internet technology has made social media platforms such as TikTok more popular among young people, especially adolescents and young adults. However, these platforms also pose risks, especially for young users. The research method used is library research. Data and information collection from various sources such as books, journals, and other literature. Based on the results of the study, the use of TikTok social media shows a significant impact on adolescent development. Although there are various benefits that can be obtained, risks and negative impacts must also be considered. Therefore, it is very important for parents, educators, and adolescents themselves to understand and manage the use of TikTok wisely, so that they can maximize the benefits while minimizing the potential negative impacts.